2013
DOI: 10.1021/ma401111n
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing of Unentangled Polymer Networks with Reversible Bonds

Abstract: Self-healing polymeric materials are systems that after damage can revert to their original state with full or partial recovery of mechanical strength. Using scaling theory we study a simple model of autonomic self-healing of unentangled polymer networks. In this model one of the two end monomers of each polymer chain is fixed in space mimicking dangling chains attachment to a polymer network, while the sticky monomer at the other end of each chain can form pairwise reversible bond with the sticky end of anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
430
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(447 citation statements)
references
References 74 publications
16
430
1
Order By: Relevance
“…Previously, Stukalin's et al 17 studied the surface welding of unentangled polymer networks. If we assume relatively higher bonding strength, the surface welding is dominated by hopping diffusion of exchangeable bonds, and the diffusivity D H is written as:…”
Section: Penetration Depth During the Welding Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Stukalin's et al 17 studied the surface welding of unentangled polymer networks. If we assume relatively higher bonding strength, the surface welding is dominated by hopping diffusion of exchangeable bonds, and the diffusivity D H is written as:…”
Section: Penetration Depth During the Welding Processmentioning
confidence: 99%
“…No matter which mechanism is chosen, CANs exhibit two features not found in traditional thermosetting polymers: malleability resulting from signicant stress relaxation, [14][15][16] and surface welding. 15,17 To further illustrate the process of BERbased surface welding effect, we drew a schematic graph as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The developed sticky reputation theory demonstrated excellent capability in predicting the dynamics of reversible networks compared with the Gonzalez's theory, which typically exhibited several orders of magnitude deviation from the experimental data, especially when the material viscous behavior was obvious. Recently, Stukhalin and coworkers 28 developed a scaling theory to investigate the self-healing process in reversible networks, which was modeled by a system consisting of dangling chains with reversible stickers at one end attached to a permanently crosslinked network at the other end. They also found that the bond lifetime was the relevant time scale for the description of the stress relaxation in reversible networks.…”
Section: Discussionmentioning
confidence: 99%
“…9 bottom right), the velocity profile is again nearly linear meaning that the shear rate is again nearly homogeneous across the gap, and that all the material is now flowing in the direction of the applied shear. Note that f has recovered to higher values (more stickers attached), which indicates that the material has self-healed: it nearly recovered all the bonds it had before the rupture [75].…”
Section: Stick-slip and Diffusionmentioning
confidence: 95%